Studi Implementasi Aplikasi Pelaporan Orang Asing (APOA) (Lembaga Pengembangan Kinerja Dosen, 2026)
The Foreign Reporting Application (APOA) is an innovation in Indonesia's immigration system aimed at improving the effectiveness of monitoring the presence of foreign nationals. This study analyzes the effectiveness of the APOA implementation by highlighting its benefits, challenges, and impacts on the immigration surveillance system. The analysis shows that APOA contributes to increased efficiency in reporting, data transparency, and the accuracy of foreign nationals' monitoring in Indonesia. The application simplifies the reporting process by enabling users to report information online, reducing human errors, and accelerating the data verification process. However, the implementation of APOA still faces several challenges, such as limited internet access in some areas, users' lack of understanding of the application, and suboptimal technology infrastructure. Therefore, improvements are needed through enhanced digital infrastructure, user training, and more supportive regulations. With these efforts, APOA is expected to become a key solution in modernizing the immigration system, making it more transparent, efficient, and responsive to global mobility dynamics.